Aquatic acute toxicity assessments of molybdenum (+VI) to Daphnia magna. (March 2016) - Wang, Chi-Wei; Liang, Chenju; Yeh, Hui-Ju
Abstract: Generally, molybdenum (Mo) metals in the environment are very rare, but wastewater discharges from industrial processes may contain high concentrations of Mo, which has the potential to contaminate water or soil if not handled properly. In this study, the impact of three common compounds of hexavalent Mo (sodium molybdate (Na2 MoO4 ‧2H2 O), ammonium molybdate ((NH4 )6 Mo7 O24 ‧4H2 O) and molybdenum trioxide (MoO3 )) in an aquatic system were assessed based on 48-h exposure acute toxicity to Daphnia magna (D . magna) . The LC50 toxicities for associated conjugate ions including Na +, Cl −, SO 4 2 −, and NH4 + were determined. Furthermore, the LC50 values for the three forms of hexavalent Mo were determined, and the acute toxicities of the Mo forms were found to follow the order: (NH4 )6 Mo7 O24 ‧4H2 O > MoO3 > Na2 MoO4 ‧2H2 O in solution. (NH4 )6 Mo7 O24 ‧4H2 O exhibited the lowest LC50 of 43.3 mg L −1 (corresponding to 23.5 mg Mo L −1 ) among the three molybdenum salts. The research confirmed that the toxicity of molybdenum in the aquatic system is highly dependent on the form of molybdenum salts used, and is also associated with the influence of the background water quality. Graphical abstract: Highlights: Impact of Mo 6+ in aquatic system via D . magna acute toxicity bioassay was studied. The acute toxicity increased in the order: Na2 MoO4 ‧2H2 O < MoO3 < (NH4 )6 Mo7 O24 ‧4H2 O. The level of Mo toxicity is highly dependent on the form of molybdenum salts. LC50 determined for Mo can be used to establish toxicity values for Mo in aquatic systems.